Implementasi Customer Relationship Management (CRM) dalam Pengembangan Loyalitas Pelanggan pada UMKM Snack Banamia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of Customer Relationship Management (CRM) in developing customer loyalty at UMKM Snack Banamia. This study examines the strategies implemented by business actors in building, maintaining, and expanding relationships with customers. The CRM framework used includes three main components, namely customer acquisition, customer retention, and customer expansion. Data were obtained through in-depth interviews, observations, and questionnaires of loyal customers. The results of the study indicate that the implementation of CRM at Snack Banamia has been carried out simply, with a personal approach and has not been digitized. Customer retention is the most prominent CRM component in practice. This study recommends the development of a more structured and technology-based CRM system to increase effectiveness in building customer loyalty sustainably.